Reformas al art. 25 de la Ley Orgánica de Comunicación para permitir la difusión de procesos judiciales - Arpi Riofrio, Cecilia Del Carmen (2015)
According to Art.25 of the Communications Law , "Position of the media on legal issues - . The media shall not take institutional positions on the innocence or guilt of the people who are involved in a legal investigation or prosecution until the criminal conviction by a competent judge ejecutoríe . The violation of this prohibition shall be punished by the Superintendency of Information and Communication with a penalty equal to 2% of the averaged turnover of the last three months of the media , made their statements to the Internal Revenue Service . In case of recidivism that takes place in the same year , the penalty will be double what is charged in each previous occasion. " The word " institutional position " evidence that the media will not report on a court case, it is very subjective and relative term position because the criteria issued by the journalist in reporting could be considered as an institutional position , therefore should clarify this statute indicating that the media will be limited to reporting on public court rulings and judgment of each of the litigants , to be broad in information. In this situation I substantiate my thesis that the Communications Law is reformed clarifying information about court proceedings and avoiding subjectivity by this provision refers to the institutional position